2018
DOI: 10.1002/jmri.25964
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter reproducibility study of diffusion MRI and fiber tractography of the lumbosacral nerves

Abstract: BackgroundDiffusion tensor imaging (DTI) has been applied in the lumbar and sacral nerves in vivo, but information about the reproducibility of this method is needed before DTI can be used reliably in clinical practice across centers.PurposeIn this multicenter study the reproducibility of DTI of the lumbosacral nerves in healthy volunteers was investigated.Study TypeProspective control series.SubjectsTwenty healthy subjects.Field Strength/Sequence3T MRI. 3D turbo spin echo, and 3.0 mm isotropic DTI scan.Assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
(91 reference statements)
1
5
0
Order By: Relevance
“…When comparing the data acquired with the same multiband factor, we found that NODDI parameters, particularly NDI and ODI, are highly reproducible between subjects and visits, while the parameter that showed the worst reproducibility is FISO. Both NDI and ODI exhibited moderate to high withinsubject reproducibility across the sessions for both SB and MB data, with CoV falling within an acceptable range for all regions (CoV < 2.5%), comparable to those obtained in similar studies for DTI parameters [40,41]. This suggests their potential to be used for exploring individual differences and potentially for clinical applications.…”
Section: Discussionsupporting
confidence: 75%
“…When comparing the data acquired with the same multiband factor, we found that NODDI parameters, particularly NDI and ODI, are highly reproducible between subjects and visits, while the parameter that showed the worst reproducibility is FISO. Both NDI and ODI exhibited moderate to high withinsubject reproducibility across the sessions for both SB and MB data, with CoV falling within an acceptable range for all regions (CoV < 2.5%), comparable to those obtained in similar studies for DTI parameters [40,41]. This suggests their potential to be used for exploring individual differences and potentially for clinical applications.…”
Section: Discussionsupporting
confidence: 75%
“…Diffusion MRI (dMRI) is a noninvasive MR technique that can provide objective, quantitative measurements that reflect microstructural nerve integrity . dMRI is based on the naturally occurring Brownian motion of water molecules.…”
mentioning
confidence: 99%
“…1 Diffusion MRI (dMRI) is a noninvasive MR technique that can provide objective, quantitative measurements that reflect microstructural nerve integrity. [4][5][6][7] dMRI is based on the naturally occurring Brownian motion of water molecules. The highly organized microstructure of a nerve's axon bundles directionally restricts diffusion (anisotropy), in comparison to an unconstrained space where water molecules freely diffuse in all directions (isotropy).…”
mentioning
confidence: 99%
“…Previous MR tractography studies of the lumbosacral plexus used several regions of interest along the nerve pathway and fiber tracking was performed with the FA threshold. [ 29 31 ] However, due to the direct proximity of skeletal muscles and peripheral nerves and the similar FA values of both tissues, [ 17 , 18 , 32 ] there is a high contamination risk from muscle fibers when MR tractography of the LSP bundles is performed. It also relies on spatial resolution and algorithm type that separation of 2 structures becomes difficult.…”
Section: Discussionmentioning
confidence: 99%